2018
DOI: 10.1002/celc.201800690
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alkali Metal Cations on the Hydrogen Evolution Reaction Activity of Pt, Ir, Au, and Ag Electrodes in Alkaline Electrolytes

Abstract: Fundamental understanding of the influence of so‐called spectator electrolyte species on the catalytic activity of electrodes is considered as a relatively novel direction in electrocatalysis. Numerous recent examples show that seemingly inert electrolyte components drastically influence the performance of catalytic centers. Even alkali metal cations in aqueous electrolytes at high pH values can change the reaction turnover frequency by orders of magnitude, depending on their nature, from Li+ to Cs+. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 23 publications
14
130
0
Order By: Relevance
“…The electrolyte composition is another parameter that can substantially modulate the overall catalyst performance. 29,[105][106][107][108] The ORR activities of various single crystalline Pt electrodes in different alkaline solutions have been investigated by Garlyyev et al 109 Interestingly, the inuence of the alkali metal cations is surface structure sensitive. As shown in Fig.…”
Section: Solvent and Electrolyte Effectsmentioning
confidence: 99%
“…The electrolyte composition is another parameter that can substantially modulate the overall catalyst performance. 29,[105][106][107][108] The ORR activities of various single crystalline Pt electrodes in different alkaline solutions have been investigated by Garlyyev et al 109 Interestingly, the inuence of the alkali metal cations is surface structure sensitive. As shown in Fig.…”
Section: Solvent and Electrolyte Effectsmentioning
confidence: 99%
“…Depending on the desired level of accuracy, these concrete observations and our tabulated values can be used to rapidly incorporate solvation into models for electrocatalysis and liquid-phase catalysis.The solvation of adsorbates is becoming a topic of great interest in computational electrocatalysis in view of the current search for more realistic representations of electrode-electrolyte interfaces. Numerous recent experimental works show that solvent and/or electrolyte effects change the activity and selectivity of electrocatalysts for important reactions such as oxygen reduction, [1,2] hydrogen evolution, [3,4] CO 2 reduction, [5,6] and CO reduction. [7,8] In addition, computational works show that solvation and/or cation coadsorption modify the adsorption energies of reaction intermediates, [9][10][11][12][13] which may not only lead to changes in reaction pathways [14] but also to considerable differences in the calculated activity of electrocatalysts.…”
mentioning
confidence: 99%
“…In electrocatalytic reactions the overpotential is mainly governed by the electrocatalyst activity, which mainly depends on its surface structure and composition . Furthermore, in recent studies the rate of the reaction is shown to be largely influenced by the so‐called spectator species in the electrolyte . Thus, the composition of the solution needs to be carefully tailored.…”
Section: Key Challenges For Alternative Oxidation Reactionsmentioning
confidence: 99%